1997
DOI: 10.1046/j.1365-2796.1997.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Low circulating leptin levels in protein‐energy malnourished chronically ill elderly patients

Abstract: ), triceps skin fold, arm muscle circumference and serum albumin, and serum orosomucoid concentrations indicating inflammatory status.Results. Patients and controls displayed body mass indexes of 17.4 Ϯ 0.7 and 25.0 Ϯ 1.1 (P Ͻ 0.001), respectively. Triceps skin fold (TSF) measurements revealed a pronounced fat depletion in the patients, being 8.5 Ϯ 0.9 and 22.3 Ϯ 1.5 mm (P Ͻ 0.001) in female and 6.1 Ϯ 0.7 and 10.8 Ϯ 0.8 mm (P Ͻ 0.001) in male patients and controls, respectively. Patient serum leptin concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
6
26
1
1
Order By: Relevance
“…The clinically low caloric intake leads primarily to the exhaustion of body fat stores that is accompanied by the lower leptin concentrations. The fact that serum leptin levels in patients with protein and energy malnutrition do not significantly correlate with BMI as found by Cederholm et al (32) and Haluzik et al (15) was supported by our study results in energy deficient marasmic malnutrition. The most likely explanation for the lack of significant associations between leptin and BMI and between leptin and oxidant/ antioxidant parameters in our marasmic group may be the presence of a threshold beyond which leptin can not decrease physiologically, since excessive loss of adipose tissue is the main characteristics of marasmus.…”
Section: Discussionsupporting
confidence: 89%
“…The clinically low caloric intake leads primarily to the exhaustion of body fat stores that is accompanied by the lower leptin concentrations. The fact that serum leptin levels in patients with protein and energy malnutrition do not significantly correlate with BMI as found by Cederholm et al (32) and Haluzik et al (15) was supported by our study results in energy deficient marasmic malnutrition. The most likely explanation for the lack of significant associations between leptin and BMI and between leptin and oxidant/ antioxidant parameters in our marasmic group may be the presence of a threshold beyond which leptin can not decrease physiologically, since excessive loss of adipose tissue is the main characteristics of marasmus.…”
Section: Discussionsupporting
confidence: 89%
“…These subjects, in fact, presented a concurrent reduction in T 3 , fT 3 and leptin plasma concentrations, and the latter showed an inverse correlation with plasma rT 3 levels in group C. Our findings seem to be in agreement with the hypothesis that body fat mass is not the only factor that regulates leptin production in chronically ill patients, and suggest a less active role for adipose tissue during catabolic processes [26].…”
Section: Discussionsupporting
confidence: 89%
“…In fact, it is known that healthy women have a severalfold increase in circulating leptin levels with respect to men, regardless of reproductive hormone status and total body fat content [27][28][29]. However, a previous study demonstrated the existence of a reduction in serum leptin concentrations and a concurrent disruption of the sexual dimorphism for leptin levels in elderly patients with chronic diseases and protein energy malnutrition [26], another condition frequently associated with an increase in plasma rT 3 concentrations [30]. Furthermore, a recent report showed that the fall in circulating leptin occurring in the metabolic adaptation to energy restriction in normal-weight humans is more evident in women than in men, suggesting that the response of leptin to a negative energy balance is regulated by gender-specific mechanisms [31], and similar results have been found in obese older individuals during weight loss [32].…”
Section: Discussionmentioning
confidence: 97%
“…Any disruption of the feedback loop in AD patients is therefore more likely to be occurring at the level of the hypothalamus or its connections. Normal functioning of the afferent limb of the leptin feedback loop in chronically ill elderly patients has previously been reported by Cederholm et al [13]. They documented significantly lower serum leptin levels in elderly proteinenergy-malnourished patients with a variety of chronic illnesses compared to healthy age-matched controls.…”
Section: Discussionmentioning
confidence: 52%